Nursing Care for Stroke Patients: Current Practice and Future Needs - Lisa A. Babkair; Razan A. Safhi; Raghad Balshram; Rahaf Safhei; Atheer Almahamdy; Fatimah Hamad Hakami; Ali Matouq Alsaleh (MDPI AG, 2023)
Background: Stroke is the second leading cause of death and the third leading cause of disability worldwide. Stroke nurses play an important role in the care of patients living with stroke by using best practices and adhering to stroke-management guidelines. This study aims at examining the current nursing practice for stroke patients in Saudi Arabia. Method: A cross-sectional descriptive design was used to collect data from nurses working in the stroke unit and intensive care unit between the period of February and June 2022 using electronic self-administered questionnaires. Results: A convenience sample of 131 nurses who provided care for stroke patients was enrolled. Significant differences in nursing practice were found between the stroke units and the intensive care units regarding the activation of the stroke code, X2 (4, N = 131) = 48.34, p < 0.001; transferring stroke patients to a designated bed, X2 (4, N = 131) = 48.74, p = 0.002; applying the NIHSS, X2 (4, N = 131) = 70.11, p < 0.001; using the modified Rankin scale, X2 (4, N = 131) = 61.24, p < 0.001; providing intervention for neglect syndrome, X2 (4, N = 131) = 44.72, and hemianopsia, X2 (4, N = 131) = 39.22; screening for poststroke depression, X2 (4, N = 131) = 101.59, p < 0.001; assessing for psychosocial needs, X2 (4, N = 131) = 74.44, p < 0.001, and encouraging patients to express their feelings, X2 (4, N = 131) = 58.64, p < 0.001; educating patients and families about stroke prevention, X2 (4, N = 131) = 40.51, p < 0.001. Conclusion: As per the results of the study, there is an urgent need for stroke units run by specialized stroke nurses to provide early stroke management and improve survivors' outcomes. Structured stroke-care programs are needed to improve nursing practice and meet the international standard of stroke care.